Tobacco chewing and associated factors among youth of Western Nepal: A cross-sectional study - S H Subba; V S Binu; R G Menezes; J Ninan; M S Rana (Wolters Kluwer Medknow Publications, 2011)
Background: Smokeless tobacco is found to be as addictive and harmful as smoking but have not been explored into, especially among youth. Objectives: This study was conducted to find the prevalence of tobacco chewing among college students in Nepal and the factors that have influence over their use. Study design: A cross-sectional study with a self-administered questionnaire. Materials and Methods: Five colleges of different streams in Pokhara city were selected for the study. A total of 816 students participated. The study was conducted during the period of May 2006-February 2007, using a semi-structured, self-administered questionnaire. Results: Overall prevalence of ever tobacco chewing was 21.3% (males 30.2% and females 10.9%) among the youth with average age of initiation 15.7 years. Pan masala and gutka were used by 63.6% and frequency of use varied widely and only 5.7% said they were daily users. Reasons cited for chewing were most commonly 'just like it' or 'friends chew'. Multiple logistic regression analysis showed age, ever smoking status, being ever alcoholic, and having friends or family members who chewed were significantly associated with students' tobacco chewing. Almost one-tenth of the students believed they were addicted to chewing tobacco and 42.5% of them had tried to quit the habit. Conclusion: The study shows a high prevalence of tobacco chewing by Nepali youth. Important factors that influenced the habit were having chewer friends, their own smoking and alcohol status and having family members who chewed. It is pertinent to consider these when formulating cessation and prevention programs